(untitled) (Sains Humanika, 2021)
This study aimed to identify the learning methods based on the flipped classroom model among UPSI’s Geography students, focusing on the students who have completed university education courses including the courses that implement flipped classroom in line with the 21st Century Approach. A quantitative approach was applied in this study using a questionnaire as a research instrument. The study respondents included 92 samples from a total population of 120 students selected through simple random sampling. The questionnaire items constructed involved three variables, namely knowledge, readiness and usage of flipped classroom. A descriptive analysis was used to examine the level of knowledge, readiness and usage variables. The Pearson correlation analysis was used to examine the relationship of each study variable, and regression analysis was used for the purpose of analyzing the influence and contribution of knowledge and readiness variables on the usage of flipped classroom. The findings of the study showed that the students had a moderate level of flipped classroom knowledge (Mean=2.97, SP=0.18), a moderate level of flipped classroom readiness (Mean=2.83, SP=0.44) and a moderate level of flipped classroom usage (Mean=2.78, SP=0.42). Further, the findings of the Pearson correlation analysis showed that there was a strong and significant positive relationship between flipped classroom knowledge and flipped classroom readiness among the students (r=.508, p<0.01), moderate and significant positive relationship between flipped classroom knowledge towards flipped classroom usage among the students (r=.487, p<0.01) and a strong and significant positive relationship between flipped classroom readiness and flipped classroom usage among the students (r=.509, p<0.01). The regression analysis showed that flipped classroom readiness had given a higher influence and contribution than flipped classroom knowledge among the students. The influence of the contribution of the flipped classroom readiness variable on flipped classroom usage among the students was 25.9 percent with the values of R2=0.329, F=21.862, p<0.05. In conclusion, the prospective UPSI’s Geography educators have not yet mastered the flipped classroom learning strategies. The implications of this implementation of flipped classroom study can be used as a guide and direction for the students in increasing their knowledge and readiness as educators in carrying out a variety of activity usages through access to learning materials, in line with the 21st Century Learning goals.